Optimization of the conversion of lignocellulosic agricultural by-products to bioethanol using different enzyme cocktails and recombinant yeast strains - Mubazangi, Munyaradzi (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2011.